Sustainable energy for future needs: An imperative for a greener tomorrow - Kolakoti, Aditya; Setiyo, Muji (Mechanical Engineering for Society and Industry, 2024)
According to Worldometer, around 8.1 billion inhabitants survive on mother earth, and earth provides the most essential resources like oxygen and water for survival. However, humanity has taken advantage of available resources on earth and has started exploring them with the available technology and machinery. As a result, the rapid consumption of exhaustible energy sources like fossil fuels, the purposeful clearing of forested lands, water pollution, industrialization, and waste disposal into the environment are increasing faster. Due to these activities, the earth's ecosystem is in great danger and requires an immediate remedy to safeguard it. Therefore, relying on renewable energy sources and promoting sustainable energy for future needs is one of the possible solutions to prevent environmental damage.